2010
DOI: 10.1007/s12237-010-9334-x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Tidal Creek Fish Communities to Dredging and Coastal Development Pressures in a Shallow-Water Estuary

Abstract: To investigate the effects of dredging and associated development pressures (i.e., shoreline armoring, developed land use) on fish, three sets of paired dredged and undredged tidal creeks were surveyed within Lynnhaven River, Virginia. Fish species diversity, community abundance, biomass, and size structure were compared among creeks and related to watershed, shoreline, and physicochemical characteristics. Mean fish community characteristics (e.g., abundance) were similar among creeks; however, species-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 38 publications
0
5
1
2
Order By: Relevance
“…In the histogram for each box, the number of significantly positive (green), negative (red), and not significant (NS) (gray) observations is plotted shorelines (Gittman et al 2016a). However, the majority of observations in Box 1a were negative and included decreased species diversity and/or abundance for a wide range of assemblages including microbial communities (Bernhard et al 2012), primary producers (e.g., Sturdevant et al 2002;O'Connor et al 2011), infaunal invertebrates (e.g., Peterson et al 2000;Seitz et al 2006;Bilkovic and Mitchell 2013), nekton and fish (Bilkovic 2011;Boys et al 2012;Peterson 2014, 2015) and waterbirds (Bolduc and Afton 2003). In Box 1b, negative responses to armoring dominated the results with decreases in diversity and abundance reported for mangroves (Anthony and Gratiot 2012; Heatherington and Bishop 2012), salt marsh vegetation (Bozek and Burdick 2005), invertebrates (Seitz et al 2006;Lawless and Seitz 2014;Swamy et al 2002), and nekton and fish (e.g., Balouskus and Targett 2016;Peterson 2014, 2015).…”
Section: E2: Species Assemblagesmentioning
confidence: 99%
“…In the histogram for each box, the number of significantly positive (green), negative (red), and not significant (NS) (gray) observations is plotted shorelines (Gittman et al 2016a). However, the majority of observations in Box 1a were negative and included decreased species diversity and/or abundance for a wide range of assemblages including microbial communities (Bernhard et al 2012), primary producers (e.g., Sturdevant et al 2002;O'Connor et al 2011), infaunal invertebrates (e.g., Peterson et al 2000;Seitz et al 2006;Bilkovic and Mitchell 2013), nekton and fish (Bilkovic 2011;Boys et al 2012;Peterson 2014, 2015) and waterbirds (Bolduc and Afton 2003). In Box 1b, negative responses to armoring dominated the results with decreases in diversity and abundance reported for mangroves (Anthony and Gratiot 2012; Heatherington and Bishop 2012), salt marsh vegetation (Bozek and Burdick 2005), invertebrates (Seitz et al 2006;Lawless and Seitz 2014;Swamy et al 2002), and nekton and fish (e.g., Balouskus and Targett 2016;Peterson 2014, 2015).…”
Section: E2: Species Assemblagesmentioning
confidence: 99%
“…Whereas both riprap and bulkheads are effective at reducing tidally-driven shore erosion, hardened shorelines are unable to naturally adapt to rising seas, are less resilient during storms, and scour the nearshore sediment through wave refraction (Gittman et al, 2014;Smith et al, 2017). Ecological studies have consistently found that shoreline armoring negatively impacts the intertidal and nearshore benthic and nekton communities relative to unmodified sections of shoreline via habitat fragmentation (Peterson & Lowe, 2009), changes in nearshore erosion processes (Bozek & Burdick, 2005), increased depth of nearby waters (Toft et al, 2013), reduced species abundance and diversity (Bilkovic et al, 2006;Bilkovic & Roggero, 2008;Kornis et al, 2017;Seitz et al, 2006) at both local and landscape scales (Isdell et al, 2015), and prevention of landward migration of intertidal habitats (Bilkovic, 2011;Titus et al, 2009). The ecological and social benefits of coastal wetlands (e.g., Mitsch & Gosselink, 2015) typically center around storm surge protection (Spalding et al, 2014;Shephard & Grimes, 1983), water quality enhancement (Bilkovic et al, 2017a;Erwin, 2009;Nelson & Zavaleta, 2012;Zedler & Kercher, 2005), habitat provision (Angelini et al, 2015;Isdell, Bilkovic & Hershner, 2018;Rozas & Minello, 1998), and carbon sequestration (Davis et al, 2015;Mcleod et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the effects of habitat fragmentation by deepening of channels and removal of wetland vegetation in Lake Huron (Uzarski et al ., ), damage to commercial fisheries from marine sand mining in Korea (Kim & Grigalunas, ), the response of the fish community to the dredging operations of coastal rivers in the BioBio region in Chile (Ortiz‐Sandoval et al ., ), the response of tidal creek fishes to dredging and coastal development pressures in Lynnhaven River (Chesapeake Bay) (Bilkovic, ), interannual changes in benthic fish populations in the eastern region of the English Channel after sand and gravel mining (Drabble, ), and harbour construction effects on reef fish communities in north‐east Brazil (Freitas et al ., ), are types of indicators reported. Experiments evaluating the risks of prolonged exposure to high concentrations of suspended sediment (SS) in orange‐spotted grouper Epinephelus coioides (Hamilton 1822), an important mariculture species that has a wide distribution in the Indo‐Pacific, showed that damages to gill structure were evident and strongly correlated with SS concentration (Au et al ., ).…”
Section: Introductionmentioning
confidence: 99%